Sports Diplomacy in Arab Countries: Sports as Soft Power in Foreign Policy - AlSaeed, Najwa (Journal of Ecohumanism, 2024)
This paper examines the critical role of sports in Arab diplomacy, focusing on countries such as Saudi Arabia, the UAE, Qatar, and Egypt, and how they utilize sports to strengthen international relations and enhance their soft power. Building on theories of public diplomacy and soft power, the study explores how these nations use sports as a strategic tool to further political agendas, shape global perceptions, and stimulate economic growth. Through a detailed analysis of case studies and empirical data, the research emphasizes how sports diplomacy—particularly football—strengthens diplomatic ties and helps project soft power internationally. The findings reveal the growing importance of sports as an instrument of foreign policy, demonstrating its impact on global engagement and international influence in the Arab world.